Hubungan Stres dengan Kualitas Tidur pada Mahasiswa – Mahasiswi Tingkat Akhir Di STIKES Husada Mandiri Poso - Susanti, Ni Made Dewi; Kalengkongan, Desty (Journal of Islamic Medicine, 2021)
Background: Students are people who are studying in college. Stress is defined as pressure, tension or unpleasant disturbances that come from outside oneself. Sleep is a basic physiological requirement needed by humans to optimize bodily functions. Students are required to be more mature and able to think critically, especially for final year students. Difficulties experienced by students such as lack of interest in research, failure to find titles, and difficulties in finding literature, resulting in negative feelings in students which ultimately trigger stress which has an impact on mental health. Objective: Knowing the relationship of stress with sleep quality in the final year students at Stikes Husada Mandiri Poso. Research Methods: This research was a descriptive analytic type with a cross section approach. The population in this study were all final year students totaling 87 people, determination of the sample using the rule of thumbs formula so that a sample of 70 people is obtained and the sampling technique used is purposive sampling. Results: There was a significant correlation between stress and sleep quality in the final year students at STIKES Husada Mandiri Poso with a value (r = 0.249 p 0.05). Conclusion: Stress contributes to the quality of sleep in final-year students at Stikes Husada Mandiri Poso Keyword : Sleep quailty, Students, Stress